High-stability and high-ionic-conductivity solid oxide electrolyte, preparation method thereof and oxide electrolyte sheet for solid-state battery

By using a composite solvent of organic solvent and water as a ball milling medium, the microstructure of solid oxide electrolyte is optimized, and the problem of LLZO-based solid lithium batteries easily react in humid air is solved, and the solid oxide electrolyte with high stability and high ionic conductivity is achieved, which improves the application performance of lithium ion conductivity and electrolyte.

CN119764537AActive Publication Date: 2025-04-04YIBIN LIBODE NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411989036.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing LLZO-based solid lithium batteries are prone to react in humid air, affecting their electrochemical properties, and their ionic conductivity has not yet met the requirements for practical applications.

Method used

A composite solvent of organic solvent and water is used as the ball milling medium to prepare a solid oxide electrolyte precursor, and a solid oxide electrolyte with high stability and high ionic conductance is obtained through post-treatment. The method includes adjusting the ratio of organic solvent to water, optimizing the microstructure of the oxide solid electrolyte, reducing grain boundary resistance and improving ionic conductivity.

Benefits of technology

It achieves high stability and high ionic conductivity of solid oxide electrolytes, improves lithium ion conductivity, and enhances the application performance of electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764537A_ABST
    Figure CN119764537A_ABST
Patent Text Reader

Abstract

The invention discloses a high-stability and high-ionic-conductivity solid oxide electrolyte, a preparation method of the high-stability and high-ionic-conductivity solid oxide electrolyte and an oxide electrolyte sheet for a solid-state battery, and provides the preparation method of the high-stability and high-ionic-conductivity solid oxide electrolyte. The preparation method comprises the following steps: preparing a solid oxide electrolyte precursor by taking a composite solvent of an organic solvent and water as a ball milling medium, and carrying out post-treatment on the solid oxide electrolyte precursor to prepare the solid oxide electrolyte, wherein the volume ratio of the organic solvent to the water in the composite solvent is (9: 1)-(2: 8); the organic solvent comprises at least one of an aliphatic hydrocarbon solvent and an alcohol solvent. The solid oxide electrolyte precursor is prepared by using the composite solvent of the organic solvent and the water as the ball milling medium, so that the microstructure of the solid oxide electrolyte can be optimized, the relative density can be improved, and meanwhile, the content of Li2CO3 on the surface can be reduced, thereby improving the ionic conductivity of the solid oxide electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a highly stable, high ion-conducting solid oxide electrolyte and a preparation method thereof, and an oxide electrolyte sheet for a solid-state battery. Background Art

[0002] In the pursuit of high energy density, solid-state lithium batteries have attracted much attention due to their potential for high energy density. Garnet-type LLZO solid electrolyte materials have the advantages of wide electrochemical window, high room temperature ionic conductivity and chemical stability to metallic lithium, making them one of the most promising solid electrolyte materials. Although a series of progress has been made in LLZO-based research, the preparation and production of practical LLZO-based solid-state lithium batteries still face many challenges.

[0003] LLZO easily reacts in humid air to produce substances such as Li2CO3, which not only affects its electrochemical performance, but may also cause interface contact problems. In order to improve the air stability of LLZO, researchers have adopted a variety of strategies, such as surface modification, doping, and atmosphere control. For example, by forming a stable passivation layer on the surface of LLZO, the reaction with moisture and CO2 in the air can be reduced. Although the ionic conductivity of LLZO is already high among oxide solid electrolytes, it is necessary to further improve its ionic conductivity and stability in order to meet the needs of practical applications. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a highly stable and high ionic conductivity solid oxide electrolyte and a preparation method thereof and an oxide electrolyte sheet for solid-state batteries.

[0005] The present invention solves the technical problem by adopting the following technical solutions.

[0006] The present invention provides a method for preparing a highly stable and highly ionic conductive solid oxide electrolyte, comprising: using a composite solvent of an organic solvent and water as a ball milling medium to prepare a solid oxide electrolyte precursor, and then preparing a solid oxide electrolyte by post-processing the solid oxide electrolyte precursor, wherein: the volume ratio of the organic solvent to water in the composite solvent is (9:1)-(2:8), and the organic solvent comprises at least one of an aliphatic hydrocarbon solvent and an alcohol solvent.

[0007] The present invention provides a highly stable and high ionic conductivity solid oxide electrolyte prepared according to the above preparation method, wherein the composition of the solid oxide electrolyte is M1 x M2 y-LLZTO, wherein: M1 includes at least one of Al and Ga, M2 includes at least one of Mg, Nb and Sb, 0<x≤0.2, 0<y≤0.2.

[0008] The present invention provides a method for preparing an oxide electrolyte sheet for a solid-state battery, comprising: mixing the solid oxide electrolyte with a binder glue and grinding until the solvent is completely volatilized, and then pressing to obtain a green body; and then performing secondary sintering on the green body to obtain an oxide electrolyte sheet for a solid-state battery.

[0009] The present invention provides a solid-state battery, which has the above-mentioned oxide electrolyte sheet for solid-state battery.

[0010] The present invention has the following beneficial effects:

[0011] The present invention provides a highly stable, high ionic conductivity solid oxide electrolyte, a preparation method thereof, and an oxide electrolyte sheet for solid-state batteries. The preparation method of the highly stable, high ionic conductivity solid oxide electrolyte provided by the present invention comprises: using a composite solvent of an organic solvent and water as a ball milling medium to prepare a solid oxide electrolyte precursor, and then preparing the solid oxide electrolyte by post-processing the solid oxide electrolyte precursor, wherein: the ratio of the organic solvent to water in the composite solvent is (9:1)-(2:8), and the organic solvent contains at least one of an aliphatic hydrocarbon solvent and an alcohol solvent. In the above preparation method, a composite solution of an organic solvent and water is used as a ball milling medium for the oxide solid electrolyte precursor, and the morphology of the oxide solid electrolyte is regulated by adjusting the ratio of the organic solvent to water. By optimizing the microstructure of the oxide solid electrolyte, the effect of reducing the grain boundary resistance and improving the ionic conductivity is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0013] Figure 1 is a SEM of the solid oxide electrolyte prepared in Comparative Example 4;

[0014] Figure 2 is a SEM of the solid oxide electrolyte prepared in Comparative Example 5;

[0015] Figure 3 is a SEM of the solid oxide electrolyte prepared in Example 7;

[0016] Figure 4is a SEM of the solid oxide electrolyte prepared in Example 1;

[0017] Figure 5 This is a SEM image of an electrolyte sheet made from the solid oxide electrolyte prepared in Example 1;

[0018] Figure 6 This is the XRD pattern of the electrolyte sheet made from the solid oxide electrolyte prepared in Example 1. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0020] A highly stable, high ionic conductivity solid oxide electrolyte and a preparation method thereof, as well as an oxide electrolyte sheet for a solid-state battery provided in an embodiment of the present invention are specifically described below.

[0021] In a first aspect, an embodiment of the present invention provides a method for preparing a highly stable, high ionic conductivity solid oxide electrolyte, which comprises: using a composite solvent of an organic solvent and water as a ball milling medium to prepare a solid oxide electrolyte precursor, and then preparing a solid oxide electrolyte by post-processing the solid oxide electrolyte precursor, wherein: the volume ratio of the organic solvent to water in the composite solvent is (9:1)-(2:8), and the organic solvent comprises at least one of an aliphatic hydrocarbon solvent and an alcohol solvent.

[0022] The embodiment of the present invention provides a method for preparing a highly stable and highly ionic conductive solid oxide electrolyte, wherein a composite solvent of an organic solvent and water is used as a ball milling medium to prepare a solid oxide electrolyte precursor, and the uniformity and reaction rate of the mixed material are improved by ball milling, the reaction temperature is reduced, and a stable cubic phase structure is generated under low-temperature conditions of a single sintering process. The low temperature can reduce the Li2CO3 on the surface of the solid oxide electrolyte particles and reduce the residual alkali content on the surface of the particles. In addition, the use of a composite solvent of an organic solvent and water as a ball milling medium can also optimize the microstructure of the solid oxide electrolyte, making the solid oxide electrolyte particles uniform and dispersed in size, which is beneficial to the success rate of the material tableting, and the compactness of the pressed tablets is high, thereby improving the lithium ion conductivity of the overall electrolyte sheet.

[0023] In some optional embodiments, the aliphatic hydrocarbon solvent includes at least one of n-hexane and acetone, and the alcohol solvent includes at least one of methanol, ethanol, and isopropanol.

[0024] In some optional embodiments, the steps are included: dry-mixing the La source, Zr source, Ta source, M1 source and M2 source and pre-firing to remove impurities; ball-milling and drying the mixed material obtained by mixing the pre-firing material with the Li source to obtain a solid oxide electrolyte precursor, wherein the ball milling medium is a composite solvent of an organic solvent and water; and then sintering the solid oxide electrolyte precursor once and dry-milling to obtain a solid oxide electrolyte.

[0025] In some optional embodiments, the La source, Zr source, Ta source, M1 source and M2 source include one or more of oxides, nitrates and sulfates of La element, Zr element, Ta element, M1 element and M2 element, and the pre-firing temperature is 850-950° C. and the time is 8-12 hours.

[0026] In some optional embodiments, the Li source in the mixed material includes one or more of lithium carbonate and lithium nitrate, and the Li source needs to be in excess of 15%.

[0027] In some optional embodiments, the solid content of the mixed material after adding the ball milling medium is 20-30%, and then the mixed material is continuously ball milled for 10-14 hours using a planetary ball mill at a ball-to-material mass ratio of 5-7:1. The ball-to-material mass ratio here refers to the mass ratio of the zirconia ball to the mixed material.

[0028] In some optional embodiments, the primary sintering temperature is 850°C-950°C, and the time is 9-15h. If the sintering temperature is too low, lithium is not fully incorporated, the raw materials are not reacted, and the LLZTO crystal shape is poor and cannot be fully utilized; if the sintering temperature is too high, Li overflows from the LLZTO crystal structure, and LLZTO has a lithium-poor structure, which hinders the migration of lithium ions and reduces ion conductivity.

[0029] In a second aspect, an embodiment of the present invention provides a highly stable and highly ionic conductive solid oxide electrolyte prepared according to the above preparation method, wherein the composition of the solid oxide electrolyte is M1 x M2 y -LLZTO, wherein: M1 includes at least one of Al and Ga, M2 includes at least one of Mg, Nb and Sb, 0<x≤0.2, 0<y≤0.2.

[0030] In a third aspect, an embodiment of the present invention provides a method for preparing an oxide electrolyte sheet for a solid-state battery, comprising: mixing the above-mentioned solid oxide electrolyte with a glue solution and grinding until the solvent is completely evaporated, and then pressing to obtain a green body; and then performing secondary sintering on the green body to obtain an oxide electrolyte sheet for a solid-state battery.

[0031] In some optional implementations, the following conditions are met:

[0032] (1) the binder is selected from at least one of PVA and PVB, the concentration of the binder glue is 4-8wt%; the amount of the binder glue added is 3-6wt% of the mass of the solid oxide electrolyte;

[0033] (2) pressing the ground powder at 14-16 MPa for 2-5 min to obtain a green body;

[0034] (3) The green body is placed in a corundum crucible and buried with a solid oxide electrolyte, and then sintered at 1100-1200° C. for 3-8 hours to obtain an oxide electrolyte sheet for solid-state batteries.

[0035] In a fourth aspect, an embodiment of the present invention provides a solid-state battery having the above-mentioned oxide electrolyte sheet for solid-state battery.

[0036] The present invention will be further described below in conjunction with the embodiments.

[0037] Example 1

[0038] A method for preparing a high-stability, high-ion-conductivity solid oxide electrolyte sheet, wherein the solid oxide electrolyte is composed of Al 0.1 Sb 0.12 -LLZO; comprising the following steps:

[0039] Step 1: According to Al 0.1 Sb 0.12 -Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Stoichiometric ratio of La2O3, ZrO2, Al2O 3、 Ta2O5 and Sb2O3 were calcined at 850℃ for 10 hours.

[0040] Step 2: Li2CO3 is mixed with La2O3, ZrO2, Al2O3, Ta2O5 and Sb2O3 pre-calcined in step 1 according to a stoichiometric ratio, wherein Li2CO3 is 15% in excess to compensate for the volatilization of lithium during the sintering process, and the mixed material is continuously ball-milled for 12 hours in a planetary ball mill at a ball-to-material mass ratio of 5:1, and the ball-milling medium is a composite solvent of an organic solvent and water; after ball-milling, the ball-milled sample is dried to obtain a solid oxide electrolyte precursor. The ratio of organic solvent to water in the mixed solution is 6:4, and the organic solvent is anhydrous ethanol.

[0041] Step 3: sinter the solid oxide electrolyte precursor once at a sintering temperature of 900° C. for 10 h; then dry-mill the sintered powder until there is no granularity, thereby obtaining a solid oxide electrolyte.

[0042] Step 4: Weigh an appropriate amount of solid oxide electrolyte, add 5wt% PVB glue (solvent is NMP), grind until the solvent evaporates completely, pour the ground powder into the mold through weighing paper, and use a powder press to maintain a pressure of 15MPa for 3 minutes to obtain a green body.

[0043] Step 5: Place the green body into a corundum crucible and bury it with a solid oxide electrolyte, and perform secondary sintering in a high-temperature muffle furnace at a temperature of 1150° C. for 5 hours to obtain an oxide electrolyte sheet for solid-state batteries.

[0044] Example 2

[0045] The steps are similar to those in Example 1, except that in step 1, the content of M1: Al is 0.05, and the content of M2: Sb is 0.05.

[0046] Example 3

[0047] The steps are similar to those of Example 1, except that: in step 1, the content of M1: Al is 0.2, and the content of M2: Sb is 0.2.

[0048] Example 4

[0049] The steps are similar to those in Example 1, except that: in step 1, the Ga content of M1 is 0.1, and the Mg content of M2 is 0.18.

[0050] Example 5

[0051] The steps are similar to those of Example 1, except that: in step 1, the content of M1: Al is 0.08, and the content of M2: Nb is 0.1.

[0052] Example 6

[0053] The steps are similar to those in Example 1, except that in step 2, the volume ratio of anhydrous ethanol to water is 9:1.

[0054] Example 7

[0055] The steps are similar to those in Example 1, except that in step 2, the volume ratio of anhydrous ethanol to water is 2:8.

[0056] Example 8

[0057] The steps are similar to those in Example 1, except that in step 2, the volume ratio of anhydrous ethanol to water is 5:5.

[0058] Example 9

[0059] The steps are similar to those in Example 1, except that: in step 3, the sintering is performed at 850°C for 8h.

[0060] Example 10

[0061] The steps are similar to those in Example 1, except that: in step 3, the sintering is performed at 950°C for 12 hours.

[0062] Embodiment 11

[0063] The steps are similar to those in Example 1, except that: in step 5, the sintering temperature is 1100° C. for 3 h.

[0064] Example 12

[0065] The steps are similar to those in Example 1, except that: in step 5, the sintering temperature is 1200° C.-8 h.

[0066] Comparative Example 1

[0067] The steps are similar to those of Example 1, except that: in step 1, there are no M1 and M2 sources.

[0068] Comparative Example 2

[0069] The steps are similar to those of Example 1, except that: in step 1, there is no M1 source.

[0070] Comparative Example 3

[0071] The steps are similar to those of Example 1, except that: in step 1, there is no M2 source.

[0072] Comparative Example 4

[0073] The steps are similar to those in Example 1, except that in step 2, the grinding medium is water.

[0074] Comparative Example 5

[0075] The steps are similar to those in Example 1, except that in step 2, the grinding medium is anhydrous ethanol.

[0076] Comparative Example 6

[0077] The steps are similar to those in Example 1, except that: in step 3, the sintering temperature is 700° C.-10 h.

[0078] Comparative Example 7

[0079] The steps are similar to those in Example 1, except that: in step 3, the sintering temperature is 1000° C.-10 h.

[0080] Comparative Example 8

[0081] The steps are similar to those in Example 1, except that: in step 5, the sintering is performed at 1250° C. for 5 h.

[0082] Comparative Example 9

[0083] The steps are similar to those in Example 1, except that: in step 5, the sintering temperature is 1050° C.-5 h.

[0084] Test Results

[0085] 1. The solid oxide electrolytes of Example 1, Example 7 and Comparative Example 4 and Comparative Example 5 were sampled and tested by scanning electron microscope.

[0086] In the preparation process of solid oxide electrolyte, the preparation of solid oxide electrolyte precursor is very important. Due to the differences in polarity and molecular structure between water and anhydrous ethanol, the grinding effect and distribution of each raw material are different during the ball milling process. Water and anhydrous ethanol affect the particle morphology and distribution of subsequent materials. Specifically: If water is used as the ball milling medium, the particles stick together and the dispersion is poor (taking comparative example 4 as an example, see Figure 1 ), if pure anhydrous ethanol is used as the ball milling medium, the particle size in the mixed material is small and the dispersibility is improved (taking comparative example 5 as an example, see Figure 2 ); and with the addition of water to the ball milling medium, small particles combine to form large particles (for example, see Example 7 Figure 3 ); the amount of water added gradually increases, the proportion of large particles gradually increases, and finally a block is formed. When the volume ratio of anhydrous ethanol to water is 6:4, the particles are round and uniform in size (taking Example 1 as an example, see Figure 4 ). For further information, the SEM and XRD diagrams of the electrolyte sheet prepared using the solid oxide electrolyte prepared in Example 1 are shown in Figure 5 and Figure 6 It can be seen from the figure that the oxide electrolyte sheet particles are tightly arranged and have high density. It can be clearly observed from the electrolyte diffraction pattern that the diffraction peak is sharp, indicating that the synthesized electrolyte has a relatively high crystallinity. In addition, compared with the standard card, the electrolyte is a cubic phase, which is conducive to the performance of lithium ion conductivity.

[0087] 2. Li2CO3 test:

[0088] A high-frequency infrared carbon-sulfur analyzer is used, and a high-frequency induction furnace is used to "burn" the carbon and sulfur components in the sample into CO2 and SO2, so as to separate them from the matrix elements. An infrared detector is then used to measure the energy attenuation law of CO2 and SO2 after selective absorption of infrared light. After computer data processing, the carbon and sulfur content in the sample is analyzed, and then the Li2CO3 content W is calculated using the following formula.

[0089] W=W0*M1 / M0

[0090] Where: W0 is the tested CO2 content (%), M1 is the chemical formula molecular weight of Li2CO3 (g / mol), M0 is the chemical formula molecular weight of CO2 (g / mol)

[0091] 3. Relative density test:

[0092] The actual density of the solid electrolyte sheet was measured in anhydrous ethanol by the Archimedes method, and the calculation formula is as follows:

[0093]

[0094] Where: w0 is the mass of the dry sample in air (g), w1 is the mass of the sample in anhydrous ethanol after being fully immersed in anhydrous ethanol (g), w2 is the mass of the sample in air after being fully immersed in anhydrous ethanol (g), ρ w is the density of anhydrous ethanol, take 0.789 g / cm 3 The relative density of the electrolyte is r The calculation formula is:

[0095]

[0096] In the above formula: ρ0 is the theoretical density of the electrolyte (g / cm 3 ), can be calculated by the formula

[0097]

[0098] Where: M is the molecular weight of the electrolyte (g / mol), NA is the Avogadro constant (mol -1 ), V is the theoretical unit cell volume of the electrolyte (cm 3 )

[0099] 4. Lithium ion conductivity test:

[0100] The sintered solid electrolyte sheet was mirror-polished on a polishing machine with 800, 1200, 1500, and 2000 mesh silicon carbide sandpaper. The polished solid electrolyte was cleaned with ethanol, ultrasonically removed surface impurities, and dried. Then, the upper and lower surfaces of the solid electrolyte sheet were coated with high-temperature silver paste, dried at 150°C for 10 minutes, and then heated to 850°C for sintering for 10 minutes, and then the electrochemical alternating current impedance (EIS) test was performed. The AC voltage amplitude in the test was 5mV, and the frequency range was 1Hz-2MHz. The ionic conductivity of the ceramic sample can be obtained according to the following formula:

[0101]

[0102] Where: d is the sample thickness (cm), S is the electrode area (cm 2 ), R is the sample resistance (Ω).

[0103] The following table shows the test results of the oxide electrolyte sheets for solid-state batteries prepared in the examples and comparative examples.

[0104]

[0105] From the table above we can see that:

[0106] (1) From the results of Examples 1-5 and Comparative Examples 1-3, it can be concluded that both elements M1 and M2 have an effect on the oxide solid electrolyte. M1 and M2 are doped into the Li and Zr positions, respectively, which affects the distribution of lithium ions in the material, causing some lithium ions to overflow and generate Li2CO3, which hinders the migration of lithium ions and reduces the lithium ion conductivity.

[0107] (2) From the results of Example 1, Examples 6-8 and Comparative Examples 4-5, it can be concluded that particle size and size distribution affect the density of the oxide electrolyte sheet. In addition, water and anhydrous ethanol have different polarities and molecular structures, so the different contents of the two will affect the distribution of the raw materials during the ball milling process, and then affect the surface Li2CO3 content. Both density and lithium carbonate will affect lithium ion conductivity.

[0108] (3) It can be seen from the results of Examples 9-10 and Comparative Examples 6-7 that the primary sintering temperature has a great influence on the Li2CO3 content. At low temperatures, part of the Li2CO3 does not participate in the reaction; as the primary sintering temperature increases, almost all of the Li2CO3 participates in the reaction and enters the crystal structure. However, if the primary sintering temperature is too high, the sintered material is too hard, which is not conducive to subsequent dry ball milling and tableting, and increases the difficulty of the process.

[0109] (4) The results of Examples 11-12 and Comparative Examples 8-9 show that the secondary temperature is mainly related to the density of the electrolyte sheet. If the sintering temperature is too low, there will be pores between the particles, the density will be low, and the migration path of lithium ions will become longer, affecting the lithium ion conductivity; if the sintering temperature is too high, the lithium ions in the crystal will migrate to the surface to form Li2CO3, which is not conducive to the performance of lithium ion conductivity.

[0110] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly stable and high ionic conductivity solid oxide electrolyte, characterized in that: It includes: A solid oxide electrolyte precursor is prepared using a composite solvent of an organic solvent and water as a ball milling medium, and the solid oxide electrolyte precursor is then post-treated to obtain a solid oxide electrolyte, wherein: the volume ratio of the organic solvent to water in the composite solvent is (9:1)-(2:8), and the organic solvent comprises at least one of an aliphatic hydrocarbon solvent and an alcohol solvent.

2. The preparation method according to claim 1, characterized in that: The aliphatic hydrocarbon solvent includes one or more of n-hexane and acetone, and the alcohol solvent includes one of methanol, ethanol and isopropanol.

3. The preparation method according to claim 1, characterized in that: The following steps are involved: La source, Zr source, Ta source, M1 source and M2 source are dry mixed and pre-fired to remove impurities; the mixed material obtained by mixing the pre-fired material with the Li source is ball-milled and dried to obtain a solid oxide electrolyte precursor, wherein: the ball milling medium is a composite solvent of an organic solvent and water; and the solid oxide electrolyte precursor is sintered once and dry-milled to obtain a solid oxide electrolyte.

4. The preparation method according to claim 3, characterized in that: The La source, Zr source, Ta source, M1 source and M2 source include one or more of the oxides, nitrates and sulfates of La, Zr, Ta, M1 and M2 elements, the pre-calcination temperature is 850-950°C, and the time is 8-12 hours; the Li source includes one or more of lithium carbonate and lithium nitrate, and the Li source needs to be in excess of 15%.

5. The preparation method according to claim 3, characterized in that: The solid content of the mixed material after adding the ball milling medium is 20-30%, and then the mixed material is continuously ball milled for 10-14 hours using a planetary ball mill at a ball-to-material mass ratio of 5-7:

1.

6. The preparation method according to claim 3, characterized in that: The primary sintering temperature is 850° C.-950° C., and the time is 9-15 hours.

7. A solid oxide electrolyte prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The composition of the solid oxide electrolyte is M1 x M2 y -LLZTO, wherein: M1 includes at least one of Al and Ga, M2 includes at least one of Mg, Nb and Sb, 0<x≤0.2, 0<y≤0.

2.

8. A method for preparing an oxide electrolyte sheet for a solid-state battery, characterized in that: The method comprises: mixing the solid oxide electrolyte according to any one of claims 1 to 6 with a binder and grinding the mixture until the solvent is completely volatilized, and then pressing the mixture to obtain a green body; and then performing secondary sintering on the green body to obtain an oxide electrolyte sheet for a solid-state battery.

9. The preparation method according to claim 8, characterized in that: The following conditions are met: (1) The binder is selected from at least one of PVA and PVB, the concentration of the binder glue is 4-8wt%; the amount of the binder glue added is 3-6wt% of the mass of the solid oxide electrolyte; (2) pressing the ground powder at 14-16 MPa for 2-5 min to obtain a green body; (3) placing the green body into a corundum crucible and burying it with the solid oxide electrolyte, and then sintering it at 1100-1200° C. for 3-8 hours to obtain an oxide electrolyte sheet for a solid-state battery.

10. A solid-state battery, characterized in that: The invention comprises the oxide electrolyte sheet for solid-state battery according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Industrialized preparation method of tantalum-aluminum-codoped lithium-lanthanum zirconate solid-state electrolyte

    CN109052473A

  • Oxide ceramic composite solid electrolyte and preparation method and application thereof

    CN109755637A

  • Preparation method of copper oxide combustion-supporting lithium-lanthanum-zirconium oxygen solid electrolyte material

    CN110323494A

  • Solid electrolyte sheet for solid-state battery and preparation method of solid electrolyte sheet

    CN115036566A